Challenges and Solutions in Managing Educational Operational Costs in Private Schools - Mohammad Yasin Al Imron; Muhammad Jangki Dausat (ICO EDUSHA, 2024)
Private schools face various challenges in managing educational operational costs which include limited funding sources, fluctuations in the number of students, and increasing costs of educational needs. This article aims to analyze the main challenges faced by private school managers and provide strategic solutions to overcome them. Using a qualitative approach through interviews and case studies, this research identifies factors that influence the sustainability of operational costs, such as dependence on parental donations, ineffective financial management, and minimal government subsidies. The proposed solutions include diversification of income sources, implementation of technology for administrative efficiency, as well as collaboration with external parties such as donor agencies and the private sector. These findings provide practical guidance for school administrators to optimize existing resources and improve the long-term sustainability of private school operations. Keywords: Operational costs, private schools, financial management, educational challenges, strategic solutions.